The orbital and sinonasal hemangiopericytoma, 2 case reports: - Maryam Maghbol; Mohammadjavad ashraf; Negar Azarpira (Fasa University of Medical Sciences, 2015)
Background & objective: Hemangiopericytoma is an uncommon vascular tumor derived from the pericytes of Zimmermann. . The most common location of the tumor is pelvic retroperitoneum and musculoskeletal system of the lower extremities. It is rarely seen in the head and neck area. In addition, only 0.8% to 3% of all orbital tumors and less than 5 % of primary sinonasal tumors are primary hemangiopericytoma, which demonstrates that the orbital and sinonasal cavities are rare locations for this tumor. Case: 2 cases of primary orbital and sinonasal hemangiopericytoma that were successfully treated through surgery were reported. Conclusion: Hemangiopericytoma is an uncommon vascular tumor which has a potentially malignant behavior. Histopathologic features alone do not predict the biologic behavior of the tumor but the increased cellularity, necrosis, hemorrhage and more than 4 mitotic figures per 10 high power field, may elicit a diagnosis of malignant hemangiopericytoma . The local recurrence and the distant metastasis might also occur with an incomplete excision.  The lung, bone and liver are the most common sites of distant metastasis. Thus, the long-term follow-up is recommended after the surgical removal of the tumor.